2022
DOI: 10.1371/journal.pone.0267344
|View full text |Cite
|
Sign up to set email alerts
|

Household water and food insecurity negatively impacts self-reported physical and mental health in the Vietnamese Mekong Delta

Abstract: Introduction Household food insecurity and inadequate water, sanitation, and hygiene (WASH) contribute to ill health. However, the interactions between household food insecurity, WASH and health have been rarely assessed concurrently. This study investigated compounded impacts of household food insecurity and WASH on self-reported physical and mental health of adults in the Vietnamese Mekong Delta. Materials and methods This cross-sectional survey interviewed 552 households in one northern and one southern p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Linkages between water insecurity and depression are documented among non-LGBTQ populations in diverse LMIC contexts such as Uganda (Cooper-Vince et al, 2018 ; Logie et al, 2023 ; Mushavi et al, 2020 ), Kenya (Miller et al, 2021 ), Haiti (Brewis et al, 2019 ), Vietnam (Vuong et al, 2022 ) and Nepal (Aihara et al, 2016 ). There is increasing attention to water insecurity-related mental health stressors in urban LMIC settings (Abadi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Linkages between water insecurity and depression are documented among non-LGBTQ populations in diverse LMIC contexts such as Uganda (Cooper-Vince et al, 2018 ; Logie et al, 2023 ; Mushavi et al, 2020 ), Kenya (Miller et al, 2021 ), Haiti (Brewis et al, 2019 ), Vietnam (Vuong et al, 2022 ) and Nepal (Aihara et al, 2016 ). There is increasing attention to water insecurity-related mental health stressors in urban LMIC settings (Abadi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…When food becomes contaminated, it creates a situation of lesser food supply. The study by Vuong et al, 2022 found independent correlations between lower physical and mental component scores (PCS and MCS) and household food insecurity, as well as inadequate water usage, highlighting a connection between hygiene, food insecurity, and overall health [ 11 ]. Poor hygiene in communities limits access to clean water, proper storage, and hygiene education, impacting food safety and availability and contributing to food insecurity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%